If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5xy + y = 0 Solving 5xy + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 5xy + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 5xy + 0 = 0 + -1y 5xy = 0 + -1y Remove the zero: 5xy = -1y Divide each side by '5y'. x = -0.2 Simplifying x = -0.2
| 9(x-3)-6=2(x+5)+13 | | 0=(4x+3)(x-5) | | 4x+6=-5+2x+15 | | 3x^4-6x^3+3=0 | | (x*x)+3x=(x*x)+x | | 5x+20=7x-80 | | (x*x)+3x=(x*x)+x+2 | | 7log(2x+12)=14 | | 7x-3x=15-5 | | (3x^2+2x)+(3x-12)=0 | | 6.6n-60=220 | | 2a-2b=10 | | 2x-37=50 | | 4.2x+35.4=9.8-8.6x | | 0=(8x+9)(x-5) | | 6x=22+4x | | -15=3a-3 | | 8x+35.4=9.8-8.6x | | a^2-1=-7a | | (2x-3)-(x-2)=1 | | x^2-22x+66=0 | | 6x+2=6(x+8) | | y=(7x+6)(x-4) | | 12x+48y-42= | | 5v+40=4v+50 | | 6x+19y=1 | | 12k^2-21=0 | | A=3.14(25) | | 3x-2(2x+2)=5 | | 25v^2=9 | | 2b-4=-6 | | x(4-t^2)=3t-5 |